The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0123940
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Quality of Antenatal Care Services Provided by Health Workers Using a Mobile Phone Decision Support Application in Northern Nigeria: A Pre/Post-Intervention Study

Abstract: BackgroundGiven the shortage of skilled healthcare providers in Nigeria, frontline community health extension workers (CHEWs) are commonly tasked with providing maternal and child health services at primary health centers. In 2012, we introduced a mobile case management and decision support application in twenty primary health centers in northern Nigeria, and conducted a pre-test/post-test study to assess whether the introduction of the app had an effect on the quality of antenatal care services provided by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 7 publications
5
96
1
4
Order By: Relevance
“…The results shows that the use of this application improves the quality of antenatal care in various aspects of service. These results were consistent with respondents' satisfaction which showed a statistically significant increase after using m4Change (Mcnabb et al, 2015).…”
Section: Research Results Mobile Health Utilization In Maternity Nursisupporting
confidence: 88%
See 1 more Smart Citation
“…The results shows that the use of this application improves the quality of antenatal care in various aspects of service. These results were consistent with respondents' satisfaction which showed a statistically significant increase after using m4Change (Mcnabb et al, 2015).…”
Section: Research Results Mobile Health Utilization In Maternity Nursisupporting
confidence: 88%
“…Almost all of the study show that mobile health application help mother and father to enhance health status on her pregnancy especially for working mom (Chaves et al, 2017;Premji, 2014;Jennings et al, 2016;Obasola, Mabawonku, & Lagunju, 2015;Felicie et al, 2016;Ledford et al, 2016;Mcnabb et al, 2015, Waring et al, 2014Spiby et al, 2014, Asiodu et al, 2015Rhyne & Borawski, 2014;Guerra-reyes et al, 2017;Smith) . Inline with previous study from Western countries, the 7 studies from non-Western countries including Africa, India, Bangladesh, Australia found that mobile health can give positive impact for pregnant mom Balakrishnan et al, 2016;Forti, Stapleton, & Kildea, 2013;Huq, Azmi, Quaiyum, & Hossain, 2014;Khatun et al, 2015;Lupton & Pedersen, 2016;Khatun et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…These studies provide some evidence for same. For example, McNabb et al (2015) developed a mobile application to collect patient antenatal data and provide primary healthcare workers with assisted guidance when treating patients, which resulted in improvements in the service provided by workers. Other organizational challenges include corruption in the Nigerian government, resistance to adoption among end users (Benson, 2011a), and the role of culture.…”
Section: Organizationalmentioning
confidence: 99%
“…For example, it is argued that electronic medical records have the potential to transform health data collection in Nigeria at a low cost (Thompson et al, 2010). Further more recent research purports their mobile health intervention provides a low cost means of collecting patient data and assisting primary health workers in delivering high quality care (McNabb et al, 2015). Financing remains a key issue on a practical level in Nigeria.…”
Section: Financialmentioning
confidence: 99%
See 1 more Smart Citation